Efek Nefroprotektif Ekstrak Bunga Telang (Clitoria ternatea L.) Pada Tikus Model Nefrotoksisitas: Analisis Biokimia, Histopatologi, Antioksidan, dan Sitokin - Asyrun Alkhairi Lubis; Novitaria Br Sembiring; Razoki Razoki; Citra Alvia Nazmi Siregar; Ade Yasmin Kaban; Qori Tari Jelitta Pandiangan; Kristia Andini Sitanggang (Journal of Pharmaceutical and Sciences, 2026)
Background: Butterfly pea flower (Clitoria ternatea L.) is rich in antioxidants and bioactive compounds that may protect the kidney from nephrotoxic injury. Objective: This study aimed to evaluate the nephroprotective effect of ethanolic extract of butterfly pea flower in gentamicin-induced rats. Methods: This in vivo experimental study used 30 male Wistar rats divided into five groups: normal control, negative control, and three treatment groups receiving butterfly pea flower extract at doses of 100, 200, and 400 mg/kgBW. The extract was administered orally, while gentamicin 100 mg/kgBW was given intraperitoneally. Parameters observed included BUN, urea, IL-6, TNF-α, renal morphology, kidney weight, and histopathology. Results: Gentamicin increased BUN, urea, IL-6, and TNF-α levels and caused histopathological damage and morphological changes in the kidney. Administration of butterfly pea flower extract reduced inflammatory response, improved histopathology, and restored renal morphology and kidney weight toward normal. The best histopathological improvement was observed at 200 mg/kgBW, whereas the strongest anti-inflammatory effect was found at 400 mg/kgBW. Conclusion: Ethanolic extract of butterfly pea flower has potential as a nephroprotective agent against gentamicin-induced nephrotoxicity.